2019
DOI: 10.1371/journal.pone.0219663
|View full text |Cite|
|
Sign up to set email alerts
|

Health risks associated with social isolation in general and in young, middle and old age

Abstract: Introduction Health effects of social isolation are well-studied at older age, in English-speaking countries, for individual health conditions, and based on unidimensional measures of isolation. Hardly any evidence exists for younger ages, for continental European and particularly German-speaking countries and based on multidimensional measures of isolation. This study therefore aimed to examine prevalence rates and associations of social isolation with various health conditions and behaviors in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 43 publications
9
104
0
3
Order By: Relevance
“…Moreover, these authors also found that a disproportionate number of men in the community were immigrants struggling with issues of social integration. This finding is consistent with a wider body of research indicating high rates of loneliness and isolation among young millennial men [30,63], as well as many other psychosocial difficulties in the transition to adulthood [31][32][33][34][35][36].…”
Section: Why Join the Community?supporting
confidence: 89%
“…Moreover, these authors also found that a disproportionate number of men in the community were immigrants struggling with issues of social integration. This finding is consistent with a wider body of research indicating high rates of loneliness and isolation among young millennial men [30,63], as well as many other psychosocial difficulties in the transition to adulthood [31][32][33][34][35][36].…”
Section: Why Join the Community?supporting
confidence: 89%
“…Currently, international guidelines recommend at least 150 min per week of physical activity, but it has been suggested that, during the confinement period, physical activity should be increased to at least 200 min per week to compensate for the decrease in the normal daily levels (Jiménez-Pavón et al, 2020). Furthermore, social isolation per se is associated with low levels of physical activity and poor diet in a population of young European adults (Hämmig, 2019), although the influence might extend to a wide range of ages since it has also been associated with smoking among older adults (Shankar et al, 2011;Kobayashi and Steptoe, 2018). Also, several studies have linked quarantine to negative psychological effects such as stress, anger, and post-traumatic stress-symptoms (Brooks et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Overall as well as subgroup reductions of weekly PA might be explained for the lack of social support and the feelings of loneliness, which have been associated with lower levels of PA and poor health conditions in both younger and older adults [36,46,47]. In fact, a prolonged time of social isolation has been observed to associate with cardiovascular diseases, poor mental health, and to increase all-cause mortality [22,48].…”
Section: Discussionmentioning
confidence: 99%